2018
DOI: 10.1177/0003319718787665
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Treatment of Transplant Renal Artery Stenosis: Evaluation of Postoperative Outcomes and Risk Factors for Recurrence

Abstract: Angioplasty with or without stenting has become a well-established procedure to treat transplant renal artery stenosis (TRAS). We evaluated our experience on postoperative outcomes following the intervention and identified potential predictive factors of TRAS recurrence. Consecutive patients who underwent endovascular treatment of TRAS were retrospectively reviewed. The study end points were the technical success, 30-day postoperative complications, and the estimated glomerular filtration rate (eGFR). Thirty-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Only 35 studies provided enough data for meta-analysis. An overall summary of the included studies, size, and evidence grading can be found in Supplemental Table S1 2,4,7,12,27-77 . We propose a diagnostic and therapeutic algorithm that reflects the findings, which is displayed in Figure 2 on the basis of the frequency of reporting cutoff parameters.…”
Section: Resultsmentioning
confidence: 99%
“…Only 35 studies provided enough data for meta-analysis. An overall summary of the included studies, size, and evidence grading can be found in Supplemental Table S1 2,4,7,12,27-77 . We propose a diagnostic and therapeutic algorithm that reflects the findings, which is displayed in Figure 2 on the basis of the frequency of reporting cutoff parameters.…”
Section: Resultsmentioning
confidence: 99%
“…Standardized screening protocol using DUS may enable early detection of recurrence following endovascular procedure. [28] There are several drawbacks to this study: this was a retrospective single-center study with a small sample size and the absence of control groups, such as those who had no TRAS or those who had no symptoms or signs of TRAS. Similar to the sample of another study, the dataset was heterogeneous, and the lack of standard methodology and reporting systems are also limitations of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Also, another study reported that increased PSV could potentially serve as a predictive measure of TRAS recurrence. Standardized screening protocol using DUS may enable early detection of recurrence following endovascular procedure [28] …”
Section: Discussionmentioning
confidence: 99%